ANALYSIS OF THE ROLE OF SOCIAL MEDIA IN BRAND MANAGEMENT AND MARKETING - Oki Saputra; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
The use of social media in brand management and marketing has become increasingly important, but companies face several challenges in maximizing the potential of social media. Key issues include the need to create relevant and engaging content, overcome content fatigue, respond to algorithm changes, and proactively manage brand reputation. This study aims to explore various aspects related to the use of social media in brand management and marketing. Using a qualitative approach and case studies of several brands that actively use social media, this study investigates the role of social media in building brand awareness, effective marketing strategies, and the impact of influencer collaboration. The findings show that social media can increase brand awareness at a lower cost and with a wider reach compared to traditional media. In addition, the use of visual content and analytical tools on social media has been shown to increase the effectiveness of marketing strategies. Collaboration with influencers is also considered to have a significant impact on expanding brand reach and building more personal relationships with audiences. This study provides recommendations for companies to manage content and collaboration with influencers more carefully to improve marketing effectiveness and maintain brand reputation on social media.